Influence of sleep disorders on the behavior of individuals with autism spectrum disorder - Fadini, Cintia C.; Lamônica, Dionísia A.; Fett-Conte, Agnes C.; Osório, Elaine; Zuculo, Gabriela M.; Giacheti, Célia M.; Pinato, Luciana (Frontiers in Human Neuroscience, 2015)
The aim of this study was to investigate the correlation between sleep disorders and behavior of subjects with autism spectrum disorder (ASD) and controls subjects using specific questionnaires. A small percentage (1.8%) of control subjects had symptoms indicative of sleep-breathing disorders and nocturnal sweating. Fifty-nine percent of the subjects with autism spectrum disorder subjects had symptoms indicative of at least one sleep disorder, being sleep-breathing disorders the most commonly reported (38%). In the control group, symptoms of sleep-breathing disorders were correlated with social, thought, attention, aggression, externalizing and behavioral problems. In the autism spectrum disorder group, disorders of arousal correlated with thinking problems and disorders of excessive somnolence were correlated with thinking and behavioral problems. These results suggest that children and adolescents with ASD have a high incidence of sleep disorders, which in turn correlate with some of the behavioral aspects that they already experience. Furthermore, sleep disturbances, when present in children with typical development, also correlate with behavioral problems.